Evidentiary Challenges in AI-Mediated E-Commerce Disputes: Comparative Perspectives from the EU, US, GCC, and Islamic Law - Shatha Ismaeel; Khalid Alammari; Zinah Ghanim Younus (Justicia Islamica, 2026)
This article aims to analyse the use of artificial intelligence (AI) as an intermediary in e-commerce transactions, thereby increasing the challenges of proving damages, particularly due to algorithmic opacity, system autonomy, and the fragmentation of legal liability subjects. Using a comparative legal approach in the European Union, the United States, and Saudi Arabia in the context of the Gulf Cooperation Council (GCC), with Islamic law as an autonomous regime of proof. Using a doctrinal comparative method, the study analyses statutory instruments, judicial practices, and emerging AI regulatory initiatives to evaluate how different legal systems address evidentiary burdens and liability attribution in AI-mediated disputes. The findings demonstrate that the European Union adopts a preventive, risk-based approach to digital evidence and accountability. In contrast, the United States relies on an ex-post, fault-oriented, and fragmented adjudicatory model. In contrast, Saudi Arabia and the broader GCC remain in a transitional phase, gradually integrating electronic evidence into civil law without a comprehensive AI-specific liability framework. Crucially, the article argues that Islamic law offers a coherent and independent evidentiary framework grounded in principles such as bayyinah, qarīnah, moral accountability (amānah), and harm prevention (lā ḍarar), which are particularly relevant in addressing AI opacity by treating AI outputs as corroborative rather than determinative proof. The study proposes doctrinal and evidentiary reforms that integrate comparative legal insights with Islamic jurisprudence to enhance legal certainty, justice, and accountability in AI-driven e-commerce disputes.